Comparative Study of Existing Hierarchical Based Routing Protocols for WSN - Sinha, Apurba; Kishore, Smita; Kumar, Pramod (International Journal of Computer Sciences and Engineering, 2021)
Wireless sensor network is a type of Ad hoc network but routing protocols for WSN are different from MANET because the factors like power, communication type, node deployment etc. are different in both. WSN protocols are classified on different parameters like Network Structure and Protocol Operation. On the basis of network structure there are three types of routing protocol flat routing, hierarchical routing, and location based routing. Flat routing protocols uses flooding and hierarchical routing protocol worked base on clusters resulting hierarchical protocols are energy efficient and easily scalable. The main aim of this paper is to evaluate, analyze and compare four existing hierarchical based routing protocols named Low Energy Adaptive Clustering Hierarchy (LEACH), Threshold Sensitive Energy Efficient Sensor Network (TEEN), Adaptive Threshold Sensitive Energy Efficient Sensor Network (APTEEN), and Distance Adaptive Threshold Sensitive Energy Efficient Sensor Network (DAPTEEN).